Uma geografia de rosto humano - Dias, Maria José (CEM – Cultura, Espaço & Memória, 2021)
In different literary means, and throughout his lifetime, Miguel Torga kept drawing a human-like geography, as his senses reacted to the places he visited and walked through. With this article, we try to show how, from his native land of Trás-os-Montes, a true existential geodesic marker, Torga displayed his telluric and Iberian nature, as he kept assessing and resizing himself as a man, by the experience of meeting new places and people that he preserved in books. By that literary inscription, born of an organic and subjective reaction and of a prospective look of human horizon, the author seeks to understand the human contours that the different physical and cultural geographies produced. In this exercise, which endows the spaces with human density, and gives them identity and historicity, the notion of heritage landscape is nurtured and expanded.